Foster Kennedy Syndrome (FKS): A Case Report - Mutali Musa; Gladness Aluyi-Osa; Marco Zeppieri (Clinics and Practice, 2022)
(1) Background: Foster Kennedy syndrome (FKS) is an ophthalmological condition characterized by an insidious reduction in vision in one eye, accompanied by clinically significant papilledema in the fellow eye. The unilateral loss of vision and optic atrophy is due to compressive optic atrophy, which causes elevated intracranial pressure that leads to swelling in the fellow eye. The risk factors for FKS include the presence of mass lesions in radiographic imaging, female gender, and increased body mass index. Differential diagnoses of FKS include tumors and pseudotumor of the frontal lobe and cranial meninges. (2) Methods: We present two cases of FKS diagnosed in February 2021 and December 2021. (3) Results: A 52-year-old male with a history of poor vision in one eye after trauma complained of constant headache. Ocular examination revealed disc pallor in his right eye with disc edema in the contralateral eye. The patient was sent for computerized tomography (CT) and placed on oral prednisolone tablets. The CT scan confirmed the diagnosis of FKS. A 30-year-old female presented to the emergency department for poor vision in her left eye and headache on the left side. Medication included dexamethasone, chloramphenicol, timolol eyedrops, furosemide, and anti-oxidant tablets dispensed from a previous private eye clinic. Ophthalmoscopy showed disc pallor with 0.1 cupping and arteriolar attenuation in both eyes with macular hemorrhages in her left eye. Bilateral papilledema secondary to raised intracranial hyper-tension was suspected. CT scans showed an intracranial mass. (4) Conclusions: These two cases show the importance of ocular examination in the diagnosis of serious systemic conditions. A concise case history, extensive ocular workup, and cranial imaging with magnetic resonance imaging and/or CT scans are indicative of patients showing acute visual loss and retro-orbital pain, which can give rise to the diagnosis of sight-threatening, permanent and fatal conditions, such as FKS. Non-surgical treatments include oral steroidal therapy, radiotherapy, and chemotherapy; however, neurosurgery is normally required.